Knockdown of Herp alleviates hyperhomocysteinemia mediated atherosclerosis through the inhibition of vascular smooth muscle cell phenotype switching. (15th October 2018) - Lin, Hui; Ni, Tingjuan; Zhang, Jie; Meng, Liping; Gao, Feidan; Pan, Sunlei; Luo, Hangqi; Xu, Fukang; Ru, Guomei; Chi, Jufang; Guo, Hangyuan
Abstract: Background: Phenotypic switching of vascular smooth muscle cells (VSMCs) plays a key role in atherosclerosis. We aimed to investigate whether Homocysteine-responsive endoplasmic reticulum protein (Herp) was involved in VSMC phenotypic switching and affected atheroprogression. Methods: To assess the role of Herp in homocysteine (Hcy)-associated atherosclerosis, Herp −/− and LDLR −/− double knockout mice were generated and fed with a high methionine diet (HMD) to induce Hyperhomocysteinemia (HHcy). Atherosclerotic lesions, cholesterol homeostasis, endoplasmic reticulum (ER) stress activation, and the phenotype of VSMCs were assessed in vivo . We used siRNAs to knockdown Herp in cultured VSMCs to further validate our findings in vitro . Results: HMD significantly activated the activating transcription factor 6 (ATF6)/Herp arm of ER stress in LDLR −/− mice, and induced the phenotypic switch of VSMCs, with the loss of contractile proteins (SMA and calponin) and an increase of OPN protein. Herp −/− /LDLR −/− mice developed reduced atherosclerotic lesions in the aortic sinus and the whole aorta when compared with LDLR −/− mice. However, Herp deficiency had no effect on diet-induced HHcy and hyperlipidemia. Inhibition of VSMC phenotypic switching, decreased proliferation and collagen accumulation were observed in Herp −/− /LDLR −/− mice when compared with LDLR −/− mice. In vitro experiments demonstrated that Hcy caused VSMC phenotypic switching, promoted cell proliferation and migration; this was reversed by Herp depletion. We achieved similar results via inhibition of ER stress using 4-phenylbutyric-acid (4-PBA) in Hcy-treated VSMCs. Conclusion: Herp deficiency inhibits the phenotypic switch of VSMCs and the development of atherosclerosis, thus providing novel insights into the role of Herp in atherogenesis. Highlights: HMD-induced HHcy could independently cause atherosclerosis through activating ER stress related ATF6/Herp pathway. Herp deficiency mitigates HHcy-induced atherosclerosis in LDLR −/− mice; Herp knockdown suppresses the phenotypic switch, cell proliferation and migration of VSMCs; Herp deficiency protects against HHcy-related atherosclerosis by inhibiting the phenotypic switch of VSMCs.